Student Needs Analysis for The Development of Augmented Reality Integrated E-Modules about Particles in Science Learning (Unnes Science Education Journal, 2022)
This research was the analysis phase of the first step in the research on the development of an integrated augmented reality e-module. The purpose of this study was to analyze the needs of students and to find out the responses of students and teachers if an integrated augmented reality e-module was developed in science learning. The method used in this analytical research was a survey method using questionnaires and interviews. Respondents were 32 junior high school students and 17 science teachers in Riau Province. Based on the result of data analysis, it was known that 56.3% of students consider the subject of particles, atoms, ions, molecules as difficult subjects because they were abstract and used many terms. Meanwhile, the result of interviews with science teachers showed that respondents only used government books as a source of student learning. The survey results showed 81.3% of students need learning resources in the form of e-modules that could be accessed from their Android so that it helped understand abstract concepts. Teachers who are willing to implement augmented reality integrated e-modules reached 100%. In conclusion, this analytical research needs to be continued to the design, development, implementation and evaluation stages based on research and development procedures, using the ADDIE model to develop an augmented reality integrated e-module about particles in science learning.